Scientia Media Der Molinismus und das Faktenwissen. Mit einer Edition des Ms. BU Salamanca 156 von 1653 - Knebel, Sven (Bochumer Studien zur Philosophie, 2021)
Molinism, formerly an invective, is nowadays a topic of philosophy. This book, however, does not deal with the modern renaissance of Middle Knowledge, rather, it explores its proliferation during the 17th and 18th centuries. The focus shifts from reviewing current trends in Church History to rehearsing the metaphysics that backed up Middle Knowledge.Fact, in Molinism, is threefold: It could have been otherwise, it belongs to some possible world, it is necessarily known by the Omniscient. Whereas the classical account of God's foreknowledge rests on its being postvolitional, the Molinist qualification of this account denies that it applies to the counterfactuals. On what else then does it prevolitionally depend that God knows for sure something to happen rather than not to happen?The Salmantine Treatise on God's foreknowledge edited here provides some additional piece of evidence of a deep Molinist disagreement. Though the manuscript was ready for print in 1653, this business failed and the manuscript fell into oblivion along with its author. The Jesuit Luke Wadding (1593-1651) belongs to a number of men from Waterford who at a time, when intolerance forced Catholics into large scale emigration, hopefully turned towards Spain. He must not be confounded with his famous namesake, the Franciscan friar, who was his cousin.Molinism, formerly an invective, is nowadays a topic of philosophy. This book, however, does not deal with the modern renaissance of Middle Knowledge, rather, it explores its proliferation during the 17th and 18th centuries. The focus shifts from reviewing current trends in Church History to rehearsing the metaphysics that backed up Middle Knowledge.Fact, in Molinism, is threefold: It could have been otherwise, it belongs to some possible world, it is necessarily known by the Omniscient. Whereas the classical account of God's foreknowledge rests on its being postvolitional, the Molinist qualification of this account denies that it applies to the counterfactuals. On what else then does it prevolitionally depend that God knows for sure something to happen rather than not to happen?The Salmantine Treatise on God's foreknowledge edited here provides some additional piece of evidence of a deep Molinist disagreement. Though the manuscript was ready for print in 1653, this business failed and the manuscript fell into oblivion along with its author. The Jesuit Luke Wadding (1593-1651) belongs to a number of men from Waterford who at a time, when intolerance forced Catholics into large scale emigration, hopefully turned towards Spain. He must not be confounded with his famous namesake, the Franciscan friar, who was his cousin.